PENGARUH PRODUK DOMESTIK REGIONAL BRUTO, PENGELUARAN PEMERINTAH, DAN INFLASI TERHADAP KONSUMSI RUMAH TANGGA DI INDONESIA - Alitasari, Ni Putu Mirah; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Household consumption is a major component of gross regional domestic product, because the higher the income of a household, the higher the level of consumption. the purpose of this study are (1) to analyze the simultaneous influence of gross regional domestic product, government expenditure and inflation on household consumption in Indonesia and (2) to analyze the partial effect of gross regional domestic product, government expenditure and inflation on household consumption in Indonesia. The data used is sourced from the Central Statistics Agency (BPS) and Bank Indonesia. The data collection method used is the observational method, using multiple linear regression analysis techniques. The data used are secondary data with the number of observations is 33 provinces in Indonesia, namely in 2010 - 2018. The results show that (1) gross regional domestic product, government spending and inflation simultaneously have a significant effect on household consumption in Indonesia ( 2) Gross regional domestic product and inflation partially have a positive and significant effect on household consumption in Indonesia while government spending partially has a negative and not significant effect on household consumption in Indonesia.   Keywords: household consumption, GRDP, inflation, government expenditure